2023
DOI: 10.1186/s10020-022-00593-3
|View full text |Cite
|
Sign up to set email alerts
|

Placental DNA methylation profile as predicting marker for autism spectrum disorder (ASD)

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that impairs normal brain development and socio-cognitive abilities. The pathogenesis of this condition points out the involvement of genetic and environmental factors during in-utero life. Placenta, as an interface tissue between mother and fetus, provides developing fetus requirements and exposes it to maternal environment as well. Therefore, the alteration of DNA methylation as epigenetic consequence of gene-environmental interaction in the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 92 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…One previous study reported that exposure to phthalate could have adverse effects on epigenetic outcomes in the human placenta 13 . Ravaei et al recently reported that placental DNA methylation profiles can serve as a biomarker to predict the development of autism spectrum disorder (ASD) in fetuses 14 . Our current results confirmed that DEHP can indeed affect fetal development via aberrant DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study reported that exposure to phthalate could have adverse effects on epigenetic outcomes in the human placenta 13 . Ravaei et al recently reported that placental DNA methylation profiles can serve as a biomarker to predict the development of autism spectrum disorder (ASD) in fetuses 14 . Our current results confirmed that DEHP can indeed affect fetal development via aberrant DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal phthalate exposure is similarly associated with placental metabolic changes and adverse offspring neurodevelopmental outcomes in a large, intergenerational cohort ( Parenti et al, 2022 ). Environmental exposures in pregnancy may also drive DNA methylation changes in human placenta, altering expression of autism spectrum disorder (ASD)-relevant loci involved in synaptogenesis and neurogenesis, for example ( Ravaei et al, 2023 ).…”
Section: Studies Of Placental Disease and Neuropsychiatric Riskmentioning
confidence: 99%
“…Unlike embryonic cells (inner cell mass), cells of the trophectoderm (cells that develop into the placenta) do not undergo extensive remethylation after demethylation, thus maintaining a genome-wide hypomethylated state. [135] Since placental DNA methylation may result from the hypomethylation of the early embryo, the disturbance of the specific DNA methylation pattern may reflect the abnormal programming of early embryonic development. A growing number of studies have found that detecting the DNA methylation characteristics of the placenta can serve as a biomarker to predict long-term diseases.…”
Section: Epigenetic Modification Changesmentioning
confidence: 99%